Concerning the Unrealized Edition of Ivanhoe by Walter Scott in the Publishing House Academia - Vera V. Filicheva (Studia Litterarum)
In 1933 the historian A.I. Yakovlev made a new translation of Walter Scott’s novel Ivanhoe, providing it with an extensive introductory article and notes, for the Academia publishing house. However, the translator’s disagreement with the internal reviewers (G.G. Shpet, D.P. Svyatopolk-Mirsky and D.A. Gorbov) prevented the novel from being published. Materials preserved in RGALI allow us to reconstruct the history of this project. Shpet’s review provides a new perspective on Walter Scott’s Russian reputation as it had been outlined in the works of Yu.D. Levin and A.A. Dolinin. Refusing the novel the status of literary classics that necessitates a most accurate rendering of “every word and turn of speech” in translation, Shpet considered exactness, that was the trademark approach of the publishing house, unnecessary in this case. Svyatopolk-Mirsky pointed to some factual errors in the introductory article and notes to the novel, though Yakovlev did not agree and refused to make changes. The materials that are presented here illustrate the specifics of Academia publishing process and, to some extent, the shift in its priorities that resulted in the revision of the perspective plan.